A Literature Review on the Use of Flashcard Canva in Addressing the Educational Needs of Elementary Students - Rahma Ibtida Saumi; Syafina Annazah; Widya Wulandari; Zaitun Qamariah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the effectiveness of using Canva-based flashcards in learning, especially at the elementary school level. This study uses library research method by collecting and analyzing data from various relevant literatures, including journals, books, and previous research articles. The literature review shows that Canva-based flashcards have the potential to improve students' vocabulary acquisition, engagement in learning, and learning outcomes. The advantages of Canva-based flashcards lie in the flexibility of design, integration of attractive visual elements and ease of access. This media allows teachers to create learning materials that are interactive, innovative and in line with curriculum needs. The analysis shows that Canva as a design tool provides added value in creating effective learning media, with various studies showing increased student motivation and understanding of the material. However, challenges such as limited teacher competence in using Canva and the need for internet connectivity are also major concerns. This study concludes that Canva-based flashcards are a relevant and effective learning medium, but its implementation requires training support and adequate infrastructure.